2022
DOI: 10.3389/fpsyg.2022.1032244
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems of preschool children during the COVID-19 home quarantine: A cross-sectional study in Shanghai, China

Abstract: ObjectiveAs the coronavirus disease 2019 (COVID-19) pandemic spread across Shanghai, China, in late February 2022 and protective measures to mitigate its impact were enacted, this study aimed to estimate how home quarantine affected the mental health of preschool children in Shanghai, China and explore the association between lifestyle factors and mental health during this special period.MethodsA cross-sectional online survey of 2,110 preschool students from Shanghai, China, was conducted during May 20–25,2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Sometimes, reasons can be magical but also unexplainable. Children at this age can see the virus as an enemy and can be fearful and worried that they could transmit the virus to other members of the family, particularly to grandparents [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, reasons can be magical but also unexplainable. Children at this age can see the virus as an enemy and can be fearful and worried that they could transmit the virus to other members of the family, particularly to grandparents [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, lockdowns, the inability to attend preschool activities, the lack of any social interactions with peers, long-term experience of fear of possible illness, and other threats significantly affected the behavior of preschool children. Several studies suggested a tendency toward adverse consequences on children's emotional and behavioral function in relation to lockdowns during the COVID-19 peak [11,12,[15][16][17][25][26][27][28]. Moreover, during the time when there was no lockdown, the threat of COVID-19 disease was ubiquitous.…”
Section: Negative Consequences Of the Covid-19 Pandemic Lockdownmentioning
confidence: 99%